Infrastructure financing in Asia. - Susantono, Bambang (Asian Development Bank, 2019)
The book, copublished with World Scientific, examines current practices and new solutions that can help meet the infrastructure gap. It discusses web-based independent infrastructure investment platforms and bonds that capture infrastructure projects positive future spillover effects. It highlights the positive impact of mass transit investments on land and property values, and the possibility of taxing the increase in values to finance these investments.